Useful modifications to the robotic posterior retroperitoneoscopic approach to adrenalectomy in severely obese patients - Feng, Zuliang; Feng, David P.; Solórzano, Carmen C. (Annals of Laparoscopic and Endoscopic Surgery; Vol 2 (September 2017): Annals of Laparoscopic and Endoscopic Surgery, 2017)
In most recent years, the laparoscopic or robotic posterior retroperitoneoscopic adren-alectomy (RPRA) has been used as an alternative to the laparoscopic transabdominal ap-proach. A 12-mm Covidien blunt balloon trocar has been used for the camera port in most previous posterior retroperitoneoscopic adrenalectomy (PRA) studies. This trocar is 100 mm in length and may not be long enough to dock the camera arm of the robot particularly in obese (BMI >35 kg/m2) patients with deep and thick back walls. Here we describe a technique that uses a platform [GelPOINT mini advanced access platform (mini Gel-POINT)] for access in RPRA. A 52-year-old female with a history of multiple prior ab-dominal procedures presented with a 2 cm right adrenal mass and a BMI of 36.9 kg/m2. A 10–12 mm long trocar was used through the mini GelPOINT for the robotic camera. Two long robotic trocars were also utilized. A fourth 5 mm assistant port was added for retraction and to avoid additional costly robotic instrument. The total op-eration time was 95 minutes (docking and console times 20 and 75 minutes, respectively). Blood loss was minimal and there were no complications. The mini GelPOINT appears to be a feasible, safe and effective alternative for RPRA procedures in severely obese patients. It is associated with an easy setup, no balloon, and easy movement of the robotic camera trocar through the gel and appears to minimize subcutaneous emphysema.